Recursos didácticos y su influencia en el aprendizaje de los estudiantes de educación del quinto grado de la Unidad Educativa Aurora Estrada de Ayala y Ramirez - Ayala Acosta, Johanna Katherine (2020)
Most of the teachers do not develop or are interested in the methodological circumstances that can be applied in the student's teaching-learning activities, the chairs continue to be offered through the execution of readings associated with dictations, the exhibitions, which keeps the schoolchild in a period of indifference, not consenting to have a vision of understanding the subject on which the class is given and therefore will not have an excellent academic achievement. It is this situation that led us to carry out this research, having a sample made up of some fifth year students of basic education of the educational unit “Aurora Estrada de Ayala and Ramírez Pérez. Once the surveys of both teachers and students and the respective analysis were carried out, it was determined that teaching resources should always be used when teaching all classes for the best teaching-learning process and it is worrying that the vast majority of Sometimes they do not use them, much disinterest on the part of the teacher when executing the class in providing the appropriate pedagogical resources, motivating and that capture the attention and interest of the student, hence, in our proposal of design of didactic resources as innovative strategies For teaching learning in the area of social studies, we have games that involve the school, theatrical activity, observation, get involved with the surrounding environment and create an awareness of our culture and identity both as human beings and to love our homeland, to favor student learning and increase their triumph as students now and as prof are future.